Ответы и объяснения

  • fou
  • ученый
2013-01-12T10:51:27+00:00

1. \lim_{n \to \infty} \frac{2^{2-n}+3^{2-n}}{2^{1-n}+3^{1-n}}= \lim_{n \to \infty} \frac{9\cdot 2^{n}+4\cdot 3^{n}}{3\cdot 2^{n}+2\cdot 3^{n}}=\\=9 \lim_{n \to \infty} \frac{ 2^{n}}{3\cdot 2^{n}+2\cdot 3^{n}}+4 \lim_{n \to \infty} \frac{ 3^{n}}{3\cdot 2^{n}+2\cdot 3^{n}}=\\=9 \lim_{n \to \infty} \frac{1}{3+2^{1-n}\cdot 3^{n}}+4 \lim_{n \to \infty} \frac{1}{3^{1-n}\cdot 2^{n}+2}=\\=\frac{9}{\lim_{n \to \infty} (3+2^{1-n}\cdot 3^{n})}+\frac{4}{\lim_{n \to \infty} (2+3^{1-n}\cdot 2^{n})}

Применяем правило Лопиталя к неопределенности:

\frac{9}{\lim_{n \to \infty} (3+\frac{\frac{d(2\cdot 3^{n})}{dn}}{\frac{d2^{n}}{dn}})}+\frac{4}{\lim_{n \to \infty} (2+\frac{\frac{d(3\cdot 2^{n})}{dn}}{\frac{d3^{n}}{dn}})}}=\\=\frac{9}{\lim_{n \to \infty} (3+\frac{2^{1-n}3^{n}ln(3)}{ln(2)})}+\frac{4}{\lim_{n \to \infty} (2+\frac{2^{n}3^{1-n}ln(2)}{ln(3)})}=\\=\frac{9}{\lim_{n \to \infty} (3+\frac{(\frac{3}{2})^{n}ln(9)}{ln(2)})}+\frac{4}{\lim_{n \to \infty} (2+\frac{(\frac{2}{3})^{n}ln(8)}{ln(3)})}=\\

=\frac{9}{ (3+\frac{ln(9)\lim_{n \to \infty}((\frac{3}{2})^{n})}{ln(2)})}+\frac{4}{ (2+\frac{ln(8)\lim_{n \to \infty}((\frac{2}{3})^{n})}{ln(3)})}=\\=\frac{9}{ (3+\frac{ln(9)\lim_{n \to \infty}((\frac{3}{2})^{n})}{ln(2)})}+\frac{4}{ (2+\frac{ln(8)(\frac{2}{3})^{\lim_{n \to \infty} n}}{ln(3)})}= 0+2=2

 

2.  \lim_{n \to \infty} (\frac{2x+3}{2x+1})^{2x}=e^{\lim_{n \to \infty} 2xln(\frac{2x+3}</p>&#10;<p>{2x+1})}=e^{2\lim_{n \to \infty} xln(\frac{2x+3}{2x+1})}

Заменяем t=\frac{1}{x}

e^{2\lim_{t \to 0} \frac{ln(\frac{\frac{2}{t}+3}{\frac{2}{t}+1})}{t}}=e^{2\lim_{t \to 0} \frac{\frac{d}{dt}ln(\frac{\frac{2}{t}+3}{\frac{2}{t}+1})}{\frac{dt}{dt}}}=\\=e^{2\lim_{t \to 0} {(\frac{\frac{2}{t}+1}{\frac{2}{t}+3})(\frac{-\frac{2}{t^{2}}(1+\frac{2}{t})+\frac{2}{t^{2}}(3+\frac{2}{t})}{(1+\frac{2}{t})^{2}}}}=e^{2\lim_{t \to 0} {(\frac{4}{t^{2}(\frac{4}{t^{2}}+\frac{8}{t}+3)})}}}=\\=e^{2\lim_{t \to 0} {(\frac{4}{{3t^{2}+8t+4}})}}=e^{ {(\frac{8}{\lim_{t \to 0}({3t^{2}+8t+4})})}}=e^{2}

 

3. (\frac{ln(4x-2)}{(x-2)^{2}})'=\frac{((ln(4x-2))'(x-2)^{2}-((x-2)^{2})'(ln(4x-2))}{(x-2)^{4}}=\\=\frac{4(x-2)^{2}}{(4x-2)(x-2)^{4}}-\frac{2(x-2)ln(4x-2)}{(x-2)^{4}}=\frac{4}{(4x-2)(x-2)^{2}}-\frac{2ln(4x-2)}{(x-2)^{3}}\\ \\x=3\\ \\ \frac{4}{(12-2)(3-2)^{2}}-\frac{2ln(12-2)}{(3-2)^{3}}=0,4-2ln10

 

скоро другие добавлю